1996
DOI: 10.1161/01.cir.93.8.1515
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Volume and Its Regulatory Factors in Congestive Heart Failure After Implantation of Long-term Left Ventricular Assist Devices

Abstract: The reduction of plasma renin activity, plasma aldosterone, and arginine vasopressin occurred earlier than the reduction of plasma volume and atrial natriuretic peptide after HeartMate implantation, possibly because of decreased pulmonary congestion and improved renal perfusion. The reduction of atrial natriuretic peptide cannot be responsible for the lack of adequate decrease of plasma volume; its reduction can be taken as a marker of improved cardiac pump function and decreased atrial stretch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…This suggests that the RAAS activation in HF is importantly reduced after LVAD implantation, providing biochemical confirmation of the improvement in hemodynamic status [23]. James et al [15] also found that in BTT patients, plasma renin activity and plasma aldosterone decreased significantly from baseline to week 4, and to week 8 after implantation of LVAD. Furthermore, the reduction of RAAS activity occurred earlier than the reduction of plasma volume and plasma atrial natriuretic peptide level, suggesting the improvement of cardiac function by LVAD was associated with normalization of volume load secondary to normalization of its regulatory substances.…”
Section: Renal Hemodynamics and Physiological Pathological Changementioning
confidence: 90%
See 1 more Smart Citation
“…This suggests that the RAAS activation in HF is importantly reduced after LVAD implantation, providing biochemical confirmation of the improvement in hemodynamic status [23]. James et al [15] also found that in BTT patients, plasma renin activity and plasma aldosterone decreased significantly from baseline to week 4, and to week 8 after implantation of LVAD. Furthermore, the reduction of RAAS activity occurred earlier than the reduction of plasma volume and plasma atrial natriuretic peptide level, suggesting the improvement of cardiac function by LVAD was associated with normalization of volume load secondary to normalization of its regulatory substances.…”
Section: Renal Hemodynamics and Physiological Pathological Changementioning
confidence: 90%
“…It is also possible that improved hemodynamic status and corrected neurohormonal dysregulation [4,15] may improve renal function and contribute to prolonged survival [16]. The relationship between renal function and LVAD is complex.…”
Section: Introductionmentioning
confidence: 99%
“…Research on pulsatile device types and kidney function may have limited their generalizability to contemporary-era CF-LVAD patients. Historical physiological studies in patients who received PF-LVAD therapy have demonstrated improved systemic perfusion [20] and decreased levels of renin, aldosterone, and vasopressin [21]. Welp et al [12] demonstrated that the renin levels improved in PF-LVAD and CF-LVAD patient groups, but the improvement was more marked in the PF-LVAD group.…”
Section: What Effect Does Lvad Physiology Have On Kidney Function?mentioning
confidence: 99%
“…Specifically, atrial natriuretic peptide, aldosterone, renin, and arginine vasopressin have all been shown to decrease after LVAD placement (16). Systemic perfusion improves, as evidenced by improvement in renal, hepatic, and neurocognitive function that occurs in most patients a few weeks after LVAD placement (17,18).…”
Section: Morbidity and Mortality After Lvad Implantationmentioning
confidence: 99%